Realidad journal and its role in the philosophical field at the beginning of the first Peronism (Quinto Sol, 2025)
The journal Realidad began to be published in 1947 – just one year after Juan Domingo Perón's rise to power– under the direction of Francisco Romero, and stopped being published in 1949. It featured a significant group of intellectuals associated with the opposition, and European exiles from Franco's regime. This paper analyzes such publication, taking into account the characteristics of its editors and the philosophical discourses within it. This dual analysis reveals the political and epistemological positions of the figures associated with the philosophical field within the Realidad group and their role in the debates of the time.
Keywords: intellectuals; history of philosophy; existentialism; Peronism